Analisis Kesalahan dalam Menyelesaikan Soal Cerita Matematika ditinjau dari Gaya Belajar Siswa - Emi Lara Safitri; Sudi Prayitno; Laila Hayati; Hapipi Hapipi (Griya Journal of Mathematics Education and Application, 2021)
This study aims to describe the errors and the causes of errors in solving mathematics word context problem in the topic of absolute value. Based on Newman’s Error Analysis terms of student’s lerning styles. Error analysis must continue to be carried out so that teachers know the types, causes, and solutions to overcome student errors. This type of research is descriptive qualitative.The research subjects of class X MIA 1 SMAN 1 Janapria academic year 2020/2021 were selected by purposive sampling. To deepen the research results, 2 students were selected from each type of learning style. Data collection techniques used are learning style questionnaire, diagnostic tests, and interviews. Data analysis technique used data reduction, data presentation, and conclusion. Based on the results of the data is (i) students with visual learning style and audits mostly made errors in stage of transformation, process skill, and encoding. While students with kinesthetic learning style mostly made errors in stage of comprehension, transformation, process skill, and encoding, (ii) the causes of mistakes for both students with visual, auditory, and kinesthetic learning styles are that students less understanding of the prerequisite lessons, cannot make mathematical models, and not know the steps to solve problems.